THE RELATIONSHIP BETWEEN GENDER DIVERSITY OF THE BOARD OF DIRECTORS AND FIRM FINANCIAL PERFORMANCE (A STUDY FROM PUBLICLY LISTED INDONESIAN MANUFACTURING FIRMS) - Imanuel, Franklin (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research primarily aims to investigate the relationship between gender diversity of the board of directors and the financial performance of the manufacturing companies listed on the Indonesian Stock Exchange (IDX). The total population in this study is 147 manufacturing firms, of which, 50 firms are excluded. Hence, the total number of samples used in this research is 97. This research conducts a panel data analysis- fixed effects estimator, to examine the relationship between gender diversity and firm financial performance, using the financial data from 2011-2016 of the manufacturing firms listed on the IDX. The results of this study indicate that the boards of manufacturing firms listed on the IDX are largely dominated by male directors. In addition, the results also show insignificant causal relationship between gender diversity of the board of directors and financial performance of manufacturing firms listed on the IDX. Two main possible reasons for this to occur may include the considerably low representation of women directors on board in manufacturing firm and social adaptation by the women directors that is caused by the peer pressures. As a consequence, their unique characteristics, ways of thinking, behavior, and working styles do not affect the boardroom and firm performance; and the expected advantages of having them on board are never realized.Keywords: board of directors, financial Performance, gender diversity